Pengembangan Bahan Ajar dengan Pembelajaran Problem Based Learning Berbantuan Media Canva untuk Meningkatkan Kemampuan Menulis Teks Biografi Siswa Kelas X SMK - Dwi Muhammad Wicaksono; Teti Sobari; Heri Isnaini (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aimed to develop teaching materials based on Problem Based Learning (PBL) assisted by Canva media for teaching biography writing to tenth-grade vocational high school students and to examine their validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants were 30 tenth-grade vocational high school students. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, biography-writing tests, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The results revealed that the developed teaching materials achieved a validity score of 95%, categorized as highly valid based on evaluations by subject-matter and media experts. The practicality level reached 94%, categorized as highly practical according to students’ responses. Furthermore, the effectiveness test demonstrated an improvement in students’ biography-writing skills, as indicated by the increase in the average score from 63.47 in the pretest to 84.73 in the posttest. The Normalized Gain (N-Gain) score of 0.58 was categorized as moderate. These findings indicate that the Canva-assisted PBL teaching materials are valid, practical, and effective for use in biography-writing instruction for vocational high school students. The study contributes to innovations in Indonesian language teaching by integrating problem-based learning with digital technology to enhance students’ writing skills.